Centralisation of financial decision-making on public hospitals in the Eastern Cape province - Thanduxolo Fana; Mosekama O. Mokhele (Africa’s Public Service Delivery & Performance Review)
Background: The formal introduction of national health insurance in 2011 is making significant progress in South Africa. However, coronavirus disease 2019 (COVID-19) and the current financial situation pose a new challenge to South Africa’s ailing public health system, especially the centralisation of financial decision-making.